213k views
1 vote
(343×7^2×100)÷(10^3×7^2×3^3)=

User Lepe
by
4.9k points

1 Answer

1 vote

Explanation:


(343 * {7}^(2) * 100) / ( {10}^(3) * {7}^(2) * {3}^(3) ) \\ \\ = ( {7}^(3) * {7}^(2) * {10}^(2) ) / ( {10}^(3) * {7}^(2) * {3}^(3) ) \\ \\ = ( {7}^(3 + 2) * {10}^(2) ) / ( {10}^(3) * {7}^(2) * {3}^(3) ) \\ \\ = ( {7}^(5) * {10}^(2) ) / ( {10}^(3) * {7}^(2) * {3}^(3) ) \\ \\ = \frac{{7}^(5) * {10}^(2) }{{10}^(3) * {7}^(2) * {3}^(3) } \\ \\ = \frac{ {7}^(3) }{10 * {3}^(3) } \\ \\ = (343)/(270) \\

User Dubace
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.